2005
DOI: 10.1152/ajpendo.00379.2004
|View full text |Cite
|
Sign up to set email alerts
|

Malonyl-CoA and carnitine in regulation of fat oxidation in human skeletal muscle during exercise

Abstract: . Malonyl-CoA and carnitine in regulation of fat oxidation in human skeletal muscle during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
158
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 49 publications
(75 reference statements)
3
158
0
1
Order By: Relevance
“…Thus, van Loon et al [2] demonstrated that a 35% decrease in the rate of fat oxidation that occurred at 72% VO 2 max, was paralleled by a 65% decline in skeletal muscle free carnitine content. Furthermore, the 2.5-fold decrease in the rate of fat oxidation during exercise at 65% VO 2 max compared to control in the afore mentioned study of Roepstorff et al [17] coincided with a 50% reduction in free carnitine availability.…”
Section: Role Of Carnitine In the Regulation Of Fat Oxidationmentioning
confidence: 64%
See 2 more Smart Citations
“…Thus, van Loon et al [2] demonstrated that a 35% decrease in the rate of fat oxidation that occurred at 72% VO 2 max, was paralleled by a 65% decline in skeletal muscle free carnitine content. Furthermore, the 2.5-fold decrease in the rate of fat oxidation during exercise at 65% VO 2 max compared to control in the afore mentioned study of Roepstorff et al [17] coincided with a 50% reduction in free carnitine availability.…”
Section: Role Of Carnitine In the Regulation Of Fat Oxidationmentioning
confidence: 64%
“…Malonyl-CoA is a potent inhibitor of CPT1 activity in vitro and is a likely candidate as the intracellular regulator of the rate of long-chain fatty acid oxidation in human skeletal muscle, particularly as changes in muscle malonyl-CoA content have occurred with opposite changes in fat oxidation at rest [16]. However, despite a 122% increase in fat oxidation rates (due to depleted pre-exercise muscle glycogen content) during exercise at 65% VO 2 peak, there were no differences in muscle malonyl-CoA content compared to control [17], suggesting that malonyl-CoA does not regulate CPT1 activity during exercise. Interestingly, a reduction in intracellular pH (from 7.1 to 6.8) in vitro reduces CPT1 activity by 34-40%, independent of any physiological change in malonyl-CoA concentration [18].…”
Section: Regulation Of the Rate Of Skeletal Muscle Fat Oxidationmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, activation of AMPK has been shown to be necessary for adiponectin effects on fatty acid oxidation in skeletal muscle cells [49, 50, and 55] . AMPK activation triggers many metabolic changes that act to restore energy balance in muscle cells, such as increased glucose uptake and metabolism,and increased oxidation of fatty acids [56] . Regulation of fatty acid oxidation pathway by AMPK involves phosphorylation of acetyl-CoA carboxylase (ACC),which leads to the inhibition of ACC activity followed by a decrease in malonyl-CoA levels [56] .…”
Section: Methodsmentioning
confidence: 99%
“…AMPK activation triggers many metabolic changes that act to restore energy balance in muscle cells, such as increased glucose uptake and metabolism,and increased oxidation of fatty acids [56] . Regulation of fatty acid oxidation pathway by AMPK involves phosphorylation of acetyl-CoA carboxylase (ACC),which leads to the inhibition of ACC activity followed by a decrease in malonyl-CoA levels [56] . Adiponectin-dependent AMPK activation in skeletal musclewas associated with an increase in ACC phosphorylation and a decrease in the concentration of malonyl-CoA [52,50] .…”
Section: Methodsmentioning
confidence: 99%